What distresses sexual well-being among older adults in different cultures? A qualitative study with Slovenian and Portuguese older adults - von Humboldt, Sofia (2022)
Objective To analyze the perspectives of sexual unwellness (SU) of Portuguese and Slovenian older adults was the objective of this study. A qualitative research was carried out, in which these perceptions were analyzed at a cultural level. Methods The sample of this study consisted of 136 older participants, between 65 and 96 years of age. Participants were of two different nationalities and lived in the community. Participants were interviewed, and all interviews were carried out through the process of literal transcription and subsequent content analysis. Results Eight key mutually exclusive themes emerged from the interviews: unavailability of partner; traditional values; body restrictions; low self-esteem and well-being; poor social support; dissatisfaction with physical appearance; pain during sex; and difficulties meeting new people. Unavailability of partner was the most important theme (17.9%) for the studied sample and specifically among Portuguese participants. Conversely, difficulties meeting new people were the least reported theme (6.8%) for the entire sample. For Slovenians traditional values were most relevant with respect to feeling sexually unwell. Conclusions Older adults from two different countries reported diverse sexual experiences. Eight mutual-exclusive themes were extensively illustrated. Policy Implications These findings are evidence for cultural-adapted interventions and policy making in the context of older adults’ sexual well-being, particularly in terms of its relation with aging well.